Vascular hyporeactivity to angiotensin II induced by Escherichia coli endotoxin is reversed by N -NitroL-Arginine, an inhibitor of nitric oxide synthase - L.A. Rodrigues; J.F. Fracasso (São Paulo State University (UNESP), 2007)
Septic shock or sepsis is reported to be one of the major causes of death when followed by systemic infectious trauma in humans and other mammals. Its development leads to a large drop in blood pressure and a reduction in vascular responsiveness to physiological vasoconstrictors which, if not contained, can lead to death. It is proposed that this vascular response is due to the action of bacterial cell wall products released into the bloodstream by the vascular endothelium and is considered a normal response of the body`s defenses against infection. A reduction in vascular reactivity to epinephrine and norepinephrine is observed under these conditions. In the present study in rats, the aim was to assess whether those effects of hypotension and hyporeactivity are also related to another endogenous vasoconstrictor, angiotensin II (AII). We evaluated the variation in the power of this vasoconstrictor over the mean arterial pressure in anesthetized rats, before and after the establishment of hypotension by Escherichia coli endotoxin (Etx). Our results show that in this model of septic shock, there is a reduction in vascular reactivity to AII and this reduction can be reversed by the inhibitor of nitric oxide synthase, N -Nitro-L-Arginine (N NLA). Our results also suggest that other endogenous factors (not yet fully known) are involved in the protection of rats against septic shock, in addition to the L-arginine NO pathway.